KINERJA KEUANGAN DAERAH SEBAGAI PEMODERASI PENGARUH DANA BAGI HASIL DAN BELANJA LANGSUNG TERHADAP PERTUMBUHAN EKONOMI - Puspaningsih, Desak Putu Dwi; Aryani M., Ni Ketut Lely (E-Jurnal Akuntansi, 2016)
Well-being is a main reference describes the development of a country. High-low level of regional economic growth noticed sources of revenue and expenditure, especially revenue-sharing and direct spending, further regional financial performance is deemed necessary, in order to allocate expenditures to the realization of the reception area is so efficient that the area in question is able to implement the objectives of regional autonomy , This study aimed to get empirical evidence of financial performance as the moderating influence of local revenue-sharing and direct spending on economic growth in the District / City of Bali Province. Data collection method used was non-participant observation. The sampling method in this study is saturated samples. The analysis technique used is Moderated Regression Analysis. The analysis showed that the revenue-sharing and shopping direct positive effect on economic growth. Effect of revenue-sharing and direct spending can be moderated by the positive direction by the variable region's financial performance, while strengthening the influence of revenue-sharing and direct spending to economic growth.
Keywords: revenue-sharing; direct expenditure; financial performance; economic growth